Penentuan PENENTUAN ZONA AGROEKOLOGI UNTUK ARAHAN KOMODITAS PERTANIAN HORTIKULTURA KABUPATEN AGAM DENGAN MENGGUNAKAN BAHASA PEMOGRAMAN PYTHON - Junita, Diva (JURNAL BUANA, 2026)
The background of this research is the importance of comprehensive analysis for the proper development of agricultural commodities, one of which is through the agroecological zone approach. The research method uses a quantitative approach employing R programming to analyze agroecological zones using the if-else logic method. The results identify four main agroecological zones with varying slope characteristics. Zones suitable for horticultural crops are in Zones II, III, and VII, covering a total area of 88,108.32 hectares. X Koto District is the main vegetable production center, while fruit production is dominated by bananas, avocados, and sapodilla. R programming is used as an analytical tool due to its ability to efficiently process complex data and provide data visualizations that facilitate understanding of the analysis results. These findings are expected to improve agricultural efficiency and productivity in Tanah Datar District.